Electrolytic capacitor and manufacturing method thereof
By incorporating a solid electrolyte layer with a conductive polymer, polyalkylene glycol, and silane compound in the electrolytic capacitor, the voltage resistance characteristics are improved, addressing the limitations of existing in-situ polymerization technologies.
Patent Information
- Application Number
- JP2023171383
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-02
- Publication Date
- 2025-04-14
AI Technical Summary
Existing technologies for in-situ polymerization in electrolytic capacitors struggle to improve voltage resistance characteristics effectively.
The use of an anode body with a porous portion, a dielectric layer, and a solid electrolyte layer with a first layer comprising a conductive polymer, polyalkylene glycol, and a silane compound, where the first layer is formed through chemical polymerization in contact with the dielectric layer and polymerization liquid.
This configuration enhances the voltage resistance characteristics of electrolytic capacitors by improving the homogeneity and morphology of the solid electrolyte layer, leading to better pressure resistance and reduced equivalent series resistance (ESR).
Smart Images

Figure 2025062370000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrolytic capacitor and a method for manufacturing the same. [Background technology]
[0002] Patent Document 1 describes "a compound comprising at least one oxidizing agent and the following structural formula (I): R 1 -(OR 2 ) n -OR 1 at least one polymer characterized by: 2 may be the same or different and represent an alkylene group, optionally containing a hydroxyl group or a polyether group, and the radical R 1 may be the same or different, and each represents a hydrogen atom, C1 to C 10 Alkyl groups, C2-C 10 alkenyl, acryloyl or methacryloyl radicals, and the radical R 1 At least one of the following is CH3, -(CH2) m CH3 (wherein m = 1, 2, 3, 4, 5 or 6) 、 C2~C 10 the at least one polymer having structural formula (I) and optionally one or more additives, wherein a reaction solution is utilized for the in situ polymerization, the reaction solution comprising the at least one thiophene monomer, the at least one polymer having structural formula (I), the at least one oxidizing agent and optionally one or more additives, the reaction solution comprising the polymer having structural formula (I) in a concentration of at least 1 wt % relative to the total weight of the reaction solution.
[0003] Patent Document 2 proposes "a capacitor assembly including a capacitor element, the capacitor element including a sintered porous anode body; a dielectric disposed on the anode body; a precoat layer formed from an organometallic compound disposed on the dielectric; and a solid electrolyte disposed on the precoat layer; the solid electrolyte including an inner layer and an outer layer, the inner layer being formed from an in-situ polymerized conductive polymer and the outer layer being formed from pre-polymerized conductive polymer particles." [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 2015-515746 [Patent Document 2] Special Publication No. 2019-533304 Summary of the Invention [Problem to be solved by the invention]
[0005] In Patent Documents 1 and 2, in-situ polymerization is considered, but the proposals in Patent Documents 1 and 2 make it difficult to improve the withstand voltage characteristics of electrolytic capacitors. [Means for solving the problem]
[0006] One aspect of the present disclosure relates to an electrolytic capacitor including an anode body having a porous portion, a dielectric layer covering at least a portion of the anode body, and a solid electrolyte layer covering at least a portion of the dielectric layer, the solid electrolyte layer having a first layer, the first layer including a first conductive component, a polyalkylene glycol, and a silane compound, and the first conductive component including a first conductive polymer and a first dopant.
[0007] Another aspect of the present disclosure relates to a method for manufacturing an electrolytic capacitor, comprising: preparing an anode body having a porous portion and a dielectric layer covering at least a portion of the anode body; and forming a solid electrolyte layer covering at least a portion of the dielectric layer, wherein the forming of the solid electrolyte layer comprises forming a first layer, and the forming of the first layer comprises chemically polymerizing a raw material monomer of a first conductive polymer in a state in which the dielectric layer is in contact with a polymerization liquid, and the polymerization liquid contains the raw material monomer, a first dopant, a polyalkylene glycol, and a silane compound. Effect of the Invention
[0008] According to the present disclosure, it is possible to improve the voltage resistance characteristics of an electrolytic capacitor. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a cross-sectional view illustrating a schematic example of a capacitor element of an electrolytic capacitor according to an embodiment of the present disclosure. [Diagram 2] 1 is a cross-sectional view illustrating a schematic diagram of an electrolytic capacitor according to an embodiment of the present disclosure. [Diagram 3] 1 is an enlarged conceptual diagram illustrating a main portion of an electrolytic capacitor according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the embodiments of the present disclosure will be described with examples, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values, materials, etc. may be exemplified, but other numerical values, materials, etc. may be applied as long as the effects of the present disclosure are obtained. In addition, components of known secondary batteries may be applied to components other than the characteristic parts of the present disclosure. In this specification, when a "range of numerical value A to numerical value B" is mentioned, the range includes numerical value A and numerical value B. When multiple materials are exemplified, one of them may be selected and used alone, or two or more may be used in combination.
[0011] The electrolytic capacitor according to the present disclosure is an electrolytic capacitor having a solid electrolyte, and is also called a solid electrolytic capacitor. However, the present disclosure also includes a solid-liquid hybrid electrolytic capacitor that contains a liquid component together with a solid electrolyte. The term "capacitor" may also be rephrased as "capacitor."
[0012] The electrolytic capacitor according to the present disclosure includes an anode body having a porous portion, a dielectric layer covering at least a portion of the anode body, and a solid electrolyte layer covering at least a portion of the dielectric layer. The solid electrolyte layer has at least a first layer. The first layer includes a first conductive component, a polyalkylene glycol, and a silane compound. The first conductive component includes a first conductive polymer and a first dopant.
[0013] The polyalkylene glycol and the silane compound each have the effect of improving the morphology of the solid electrolyte layer having the first layer from different aspects. Specifically, it is believed that the polyalkylene glycol and the silane compound have the effect of improving the homogeneity of the first layer. It is believed that the silane compound has the effect of controlling the growth rate of the first layer to grow the first layer homogeneously. On the other hand, it is believed that the polyalkylene glycol controls the growth rate of the first layer and also functions as a structural skeleton of the first layer. The excellent formation of the solid electrolyte layer improves the voltage resistance characteristics of the electrolytic capacitor.
[0014] When the first layer contains polyalkylene glycol but does not contain a silane compound, it is difficult to significantly improve the pressure resistance. In addition, when the first layer contains polyalkylene glycol and a silane compound, the pressure resistance may be lower than when the first layer does not contain either polyalkylene glycol or a silane compound. Therefore, it is considered that the synergistic action of polyalkylene glycol and the silane compound is involved in the homogenization of the first layer and the improvement of the pressure resistance.
[0015] The number of carbon atoms of the oxyalkylene group (oxyalkylene monomer unit) constituting the polyalkylene glycol may be 2 or more and 5 or less, 2 or more and 4 or less, or may be 2 or 3. The number of oxyalkylene groups constituting the polyalkylene glycol may be only one type, or may be two or more types. When the number of carbon atoms of the oxyalkylene group is 2, the polyalkylene glycol is polyethylene glycol (hereinafter also referred to as "PEG"). When the number of carbon atoms of the oxyalkylene group is 3, the polyalkylene glycol is polypropylene glycol (hereinafter also referred to as "PPG"). When the number of carbon atoms of the oxyalkylene group is 4, the polyalkylene glycol is polybutylene glycol (hereinafter also referred to as "PBG"). When the number of carbon atoms of some of the oxyalkylene groups is 2 and the number of carbon atoms of the remaining oxyalkylene groups is 3, the polyalkylene glycol is a copolymer of ethylene glycol and propylene glycol (hereinafter also referred to as "PEG-co-PPG"). In addition, in PEG, PPG, PBG, PEG-co-PPG or other similar polymers, for example, 10 mol% or less or 5 mol% or less of monomer units (typically oxyalkylene units) may be different monomer units. The copolymer may be a random copolymer, a block copolymer, or a graft copolymer. The polyalkylene glycol may be used alone or in combination of two or more kinds.
[0016] Among the polyalkylene glycols, PEG, PPG and PEG-co-PPG are preferred because they are easily available and have a large effect on homogenizing the first layer. Preferred embodiments of the polyalkylene glycol to be contained in the first layer include, for example, the following. (1) Polyalkylene glycol containing 50% or more by mass of PEG (2) Polyalkylene glycol containing 50% or more by mass of PPG (3) Polyalkylene glycol containing 50% or more by mass of PEG-co-PPG (4) Polyalkylene glycol in which 80 to 100% by mass is PEG (5) Polyalkylene glycol in which 80 to 100% by mass is PEG-co-PPG
[0017] From the viewpoint of improving the withstand voltage characteristics of the electrolytic capacitor and reducing the ESR, the above embodiment (3) (polyalkylene glycol in which 80% by mass or more is PEG-co-PPG) or the above embodiment (5) (polyalkylene glycol in which 100% by mass is PEG-co-PPG) is particularly preferred. PEG-co-PPG is an insulating material, but is considered to be unlikely to aggregate on its own and to be easily dispersed uniformly in the first layer. Therefore, PEG-co-PPG is unlikely to reduce the conductivity of the first layer and is unlikely to increase the ESR of the electrolytic capacitor. PEG-co-PPG is preferably a random copolymer.
[0018] The number average molecular weight of the polyalkylene glycol is not particularly limited, but in consideration of dispersibility in the first layer, it is preferably from 200 to 5,000. The number average molecular weight of the polyalkylene glycol is a polystyrene-equivalent number average molecular weight measured using gel permeation chromatography (GPC).
[0019] The number average molecular weight of PEG is not particularly limited, but is preferably 200 or more and 5,000 or less, and more preferably 200 to 2,000, in consideration of dispersibility in the first layer.
[0020] The number average molecular weight of the PPG is not particularly limited, but is preferably 200 or more and 5,000 or less, and more preferably 200 to 3,000, in consideration of dispersibility in the first layer.
[0021] The number average molecular weight of PEG-co-PPG is preferably 1,000-3,000, and more preferably 1,000-2,000.
[0022] The polyalkylene glycol may have hydroxyl groups at both ends of the molecule. The polyalkylene glycol may be a derivative in which the hydroxyl group at at least one end of the molecule is replaced with a functional group such as an ester group, an ether group, or an amino group. Examples of the derivative include polyalkylene glycol monoester, polyalkylene glycol diester, polyalkylene glycol monoalkyl ether, and polyalkylene glycol dialkyl ether.
[0023] Specific examples of polyalkylene glycol derivatives having an ester group include polyalkylene glycol monomethacrylate, polyalkylene glycol dimethacrylate, polyalkylene glycol monoacrylate, polyalkylene glycol diacrylate, polyalkylene glycol monostearate, polyalkylene glycol monolaurate, polyoxyalkylene sorbitan monolaurate, polyoxyalkylene sorbitan monopalmitate, polyoxyalkylene sorbitan trioleate, and polyoxyalkylene sorbitan tetraoleate.
[0024] Specific examples of polyalkylene glycol derivatives having an ether group include polyalkylene glycol monomethyl ether, polyalkylene glycol dimethyl ether, polyoxyalkylene docosyl ether, polyoxyalkylene octylphenyl ether, polyoxyalkylene nonylphenyl ether, polyoxyalkylene cetyl ether, and polyoxyalkylene lauryl ether.
[0025] The content of polyalkylene glycol in the first layer is not particularly limited, but from the viewpoint of effectively suppressing an increase in ESR, it may be, for example, 10 to 15 mass %, or 18 to 23 mass %.
[0026] The ratio (Mpag / Mcp) of the mass (Mpag) of the polyalkylene glycol to the mass (Mcp) of the first conductive component contained in the first layer may be, for example, 0.15 to 0.20, or 0.25 to 0.30.
[0027] The silane compound may be a compound having a silicon atom and four radicals covalently bonded to the silicon atom. At least one of the four radicals may be a reactive functional group. The reactive functional group may be an epoxy group, a halogenated alkyl group, an amino group, a ureido group, a mercapto group, an isocyanate group, a polymerizable group, or the like. Examples of the polymerizable group include an acryloyl group, a methacryloyl group, and a vinyl group. At least one of the four radicals may be hydrolyzable. The hydrolyzable radical may be, for example, an alkoxy group such as a methoxy group, an ethoxy group, or a propoxy group, or a halogen atom such as a chlorine atom or a bromine atom, or the like.
[0028] The reactive functional group or hydrolyzable group of the silane compound may react with other components contained in the first layer, the dielectric layer, etc. Thus, the silane compound may be chemically bonded to other components contained in the first layer or the dielectric layer.
[0029] The silane compound may be derived from a silane coupling agent. The silane coupling agent is easy to obtain, easily binds to the first conductive polymer, and is easily distributed uniformly in the first layer. Therefore, when the silane coupling agent is used, the conductivity of the first layer is less likely to decrease, and the ESR of the electrolytic capacitor is less likely to increase.
[0030] Silane coupling agents having an epoxy group, silane coupling agents having an acrylic group, etc. are preferred. Silane coupling agents having an epoxy group include 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, etc. In addition, silane coupling agents having an acrylic group include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane (γ-acryloxypropyltrimethoxysilane), etc. Other silane coupling agents include vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, p-styryltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethoxysilane), Examples of the silane derivatives include methyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride, 3-ureidopropyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, and 3-isocyanatepropyltriethoxysilane. These may be used alone or in combination of two or more.
[0031] The distribution state of the silane compound in the first layer can be measured, for example, by analyzing a cross-sectional image of the first layer with an electron probe micro analyzer (EPMA). In the EPMA analysis, the silane compound is detected as elemental silicon.
[0032] The content of the silane compound in the first layer is not particularly limited, but from the viewpoint of effectively suppressing an increase in ESR, it may be, for example, 10 to 15 mass %, or 18 to 23 mass %.
[0033] The ratio (Msl / Mcp) of the mass (Msl) of the silane compound to the mass (Mcp) of the first conductive component contained in the first layer may be, for example, 0.15 to 0.20, or 0.25 to 0.30.
[0034] The ratio (Msl / Mpag) of the mass (Msl) of the silane compound to the mass (Mpag) of the polyalkylene glycol contained in the first layer may be, for example, 1.0 to 1.5, or 2.0 to 3.0.
[0035] The solid electrolyte layer may further include a second layer covering at least a part of the first layer. The second layer may include a second conductive component different from the first conductive component. The second conductive component includes a second conductive polymer and a second dopant. When the first conductive component and the second conductive component are different, the following cases are included: (i) the first conductive polymer and the second conductive polymer are different, and the first dopant and the second dopant are the same; (ii) the first conductive polymer and the second conductive polymer are the same, and the first dopant and the second dopant are different; (iii) the first conductive polymer and the second conductive polymer are different, and the first dopant and the second dopant are also different; and (iv) the first conductive component and the second conductive component are made of the same material, but have different morphologies.
[0036] The first conductive polymer and the second conductive polymer may be π-conjugated polymers. The first conductive polymer and the second conductive polymer may each independently be a conductive polymer such as polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, etc. The first conductive polymer and the second conductive polymer may each independently contain one of these conductive polymers, or may contain two or more of them. The conductive polymer may also be a copolymer of two or more monomers. Among the conductive polymers, polythiophene, polyaniline, polypyrrole, etc. are preferred in terms of excellent conductivity.
[0037] In this specification, polypyrrole, polythiophene, polyfuran, polyaniline, etc. refer to polymers having polypyrrole, polythiophene, polyfuran, polyaniline, etc. as their basic skeletons, respectively. Therefore, polypyrrole, polythiophene, polyfuran, polyaniline, etc. may also include their respective derivatives. For example, polythiophene includes poly(3,4-ethylenedioxythiophene), etc.
[0038] The first dopant and the second dopant are not particularly limited and may be a low molecular weight dopant or a high molecular weight dopant. The first dopant and the second dopant may be an acid, a salt, a complex, or the like that generates an anion that dopes the conjugated π electrons with electrons when the conductive polymer is oxidized. Examples of the anion include sulfate ions, nitrate ions, phosphate ions, borate ions, organic sulfonate ions, and carboxylate ions.
[0039] Examples of low molecular weight dopants that generate sulfonate ions include organic sulfonic acids such as p-toluenesulfonic acid and naphthalenesulfonic acid, and salts and complexes of organic sulfonic acids.
[0040] Examples of polymer dopants that generate sulfonate ions include polymers such as polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallylsulfonic acid, polyacrylic sulfonic acid, polymethacrylic sulfonic acid, poly(2-acrylamido-2-methylpropanesulfonic acid), polyisoprene sulfonic acid, aromatic polyester sulfonic acid, and phenolsulfonic acid novolac resin, as well as salts and complexes of these polymers.
[0041] The first layer is preferably allowed to penetrate into the voids of the porous portion having the dielectric layer, and therefore it is preferable to use a low molecular weight dopant for the first layer. On the other hand, it is preferable for the second layer to contain a polymer dopant in order to obtain higher stability and pressure resistance. The first dopant and the second dopant are not limited to the above specific examples. The first dopant and the second dopant may each independently contain the above material alone or two or more kinds.
[0042] At least a part of the first layer is preferably filled in the voids of the porous part having the dielectric layer. This can effectively reduce the ESR of the electrolytic capacitor. On the other hand, at least a part of the second layer may be formed on the outside of the main surface of the porous part without filling the voids. This forms a solid electrolyte layer of sufficient thickness, which is more advantageous for reducing the ESR. The outside of the main surface of the porous part means a position away from the main surface of the porous part. The main surface of the porous part means the surface of the porous part having the dielectric layer, which is hypothetically assumed when it is assumed that there are no voids.
[0043] To observe the first and second layers, a sample obtained by the following procedure can be used. First, a solid electrolytic capacitor or a capacitor element is embedded in a curable resin, and the curable resin is cured. The cured product is polished or processed with a cross-section polisher (CP) to expose a cross section parallel to the thickness direction of the solid electrolyte layer and perpendicular to the length direction of the capacitor element. In this way, a sample for measurement is obtained. By observing the sample with, for example, a scanning electron microscope (SEM), the distribution of the first and second layers in the voids of the porous part having the dielectric layer can be understood.
[0044] The first layer may be formed by in-situ polymerization. In this case, the first layer is formed by polymerizing a raw material monomer of the first conductive polymer in the presence of a porous portion having a dielectric layer. Since the raw material monomer can penetrate deep into the porous portion, at least a part of the first layer is likely to be filled in the voids of the porous portion. The raw material monomer may contain an oligomer. On the other hand, the second layer may be formed by impregnating an anode body having a dielectric layer with a liquid (solution or dispersion) containing a second conductive polymer that has been polymerized in advance, so as to cover at least a part of the first layer.
[0045] <Electrolytic capacitor> Next, the electrolytic capacitor and the manufacturing method thereof according to the present disclosure will be described with reference to the drawings as appropriate. However, the present disclosure is not limited thereto. Fig. 1 is a cross-sectional view showing an example of a capacitor element of an electrolytic capacitor. Fig. 2 is a cross-sectional schematic view of an electrolytic capacitor. Fig. 3 is a conceptual diagram showing an enlarged view of a main part of an electrolytic capacitor.
[0046] Electrolytic capacitor 20 includes a capacitor element 10 having an anode portion 6 and a cathode portion 7, an exterior body 11 that seals capacitor element 10, an anode lead terminal 13 electrically connected to anode portion 6 and partially exposed from exterior body 11, and a cathode lead terminal 14 electrically connected to cathode portion 7 and partially exposed from exterior body 11. Anode portion 6 includes an anode body 1 and an anode wire 2. A dielectric layer 3 is formed on the surface of the anode body. Cathode portion 7 includes a solid electrolyte layer 4 covering at least a portion of dielectric layer 3, and cathode layer 5 covering at least a portion of the surface of solid electrolyte layer 4.
[0047] <Capacitor element> An example of the capacitor element 10 will now be described in detail.
[0048] (Anode) The anode part 6 of the capacitor element 10 has an anode body 1 and an anode wire 2 extending from one surface of the anode body 1 and electrically connecting to an anode lead terminal 13. The anode body 1 is, for example, a rectangular porous sintered body obtained by sintering metal particles. As the metal particles, particles of a valve metal such as titanium (Ti), tantalum (Ta), or niobium (Nb) are used. The anode body 1 uses one or more types of metal particles. The metal particles may be an alloy made of two or more types of metal. The valve metal alloy contains a valve metal as a main component, for example, 50 atomic % or more of the valve metal.
[0049] The anode wire 2 is made of a conductive material. The material of the anode wire 2 is not particularly limited, and may be, for example, the valve metals mentioned above, copper, aluminum, an aluminum alloy, or the like. The materials constituting the anode body 1 and the anode wire 2 may be the same or different. The anode wire 2 has a first portion 2a embedded in the anode body 1 from one surface of the anode body 1, and a second portion 2b extending from the above surface of the anode body 1.
[0050] The anode part 6 is produced, for example, by press-molding the first portion 2a into a rectangular parallelepiped shape with the first portion 2a embedded in metal particles, followed by sintering. This causes the second portion 2b of the anode wire 2 to be drawn out so as to stand from one surface of the anode body 1. The second portion 2b is joined to the anode lead terminal 13 by welding or the like.
[0051] A dielectric layer 3 is formed on the surface of the anode body 1. The dielectric layer 3 is made of, for example, a metal oxide. Examples of methods for forming a layer containing a metal oxide on the surface of the anode body 1 include a method of anodizing the surface of the anode body 1 by immersing the anode body 1 in a chemical conversion solution, a method of heating the anode body 1 in an atmosphere containing oxygen, and a method of forming the layer by atomic layer deposition (ALD).
[0052] (cathode) The cathode section 7 has a solid electrolyte layer 4 and a cathode layer 5 covering the solid electrolyte layer 4. The solid electrolyte layer 4 is formed so as to cover at least a part of the dielectric layer 3. The solid electrolyte layer 4 includes a first layer 4a covering the dielectric layer 3 and a second layer 4b covering the first layer 4a (FIG. 3). The first layer 4a is formed, for example, by "in situ polymerization" of raw material monomers of a first conductive polymer on the dielectric layer 3.
[0053] The first layer 4a has an inner layer 104a filled in the voids of the porous part having the dielectric layer 3, and an outer layer 104b protruding from the main surface Sm of the porous part having the dielectric layer 3. The second layer 4b is formed outside the main surface Sm of the porous part without filling the voids. By increasing the thickness of the outer layer 104b protruding from the main surface Sm of the porous part having the dielectric layer 3 in this manner, it is possible to improve the adhesion between the dielectric layer 3, the first layer 4a, and the second layer 4b.
[0054] The cathode layer 5 has, for example, a carbon layer 5a formed so as to cover the solid electrolyte layer 4, and a metal paste layer 5b formed on the surface of the carbon layer 5a. The carbon layer 5a contains a conductive carbon material such as graphite and a resin. The metal paste layer 5b contains, for example, metal particles (e.g., silver) and a resin. The configuration of the cathode layer 5 is not limited to this configuration. The cathode layer 5 may have any configuration as long as it has a current collecting function.
[0055] (Anode lead terminal) One end of the anode lead terminal 13 is electrically connected to the anode body 1 via the second portion 2b of the anode wire 2. The other end of the anode lead terminal 13 is led out of the exterior body 11 and exposed from the exterior body 11. The material of the anode lead terminal 13 is not particularly limited as long as it is conductive. The anode lead terminal 13 may be made of a metal such as copper, or a non-metal. The shape of the anode lead terminal 13 is, for example, a flat plate. The thickness of the anode lead terminal 13 is, for example, 25 μm or more and 200 μm or less.
[0056] (Cathode lead terminal) The cathode lead terminal 14 is electrically connected to the cathode section 7 at a joint 14a which is one end of the cathode lead terminal 14. The joint 14a is joined to the cathode layer 5 via, for example, a conductive adhesive 8. The other end of the cathode lead terminal 14 is led out and exposed from the exterior body 11. The material of the cathode lead terminal 14 is also not particularly limited as long as it is conductive. The cathode lead terminal 14 may be made of a metal such as copper, or a non-metal. The shape of the cathode lead terminal 14 is, for example, a flat plate shape. The thickness of the cathode lead terminal 14 is, for example, 25 μm or more and 200 μm or less.
[0057] (Exterior body) The exterior body 11 is provided to seal the capacitor element 10 and to electrically insulate the anode lead terminal 13 and the cathode lead terminal 14, and is made of an insulating material. The insulating material includes, for example, a thermosetting resin. Examples of the thermosetting resin include epoxy resin, phenol resin, silicone resin, melamine resin, urea resin, alkyd resin, polyurethane, polyimide, and unsaturated polyester.
[0058] <Manufacturing method of electrolytic capacitors> An example of a method for manufacturing an electrolytic capacitor will be described below.
[0059] A method for manufacturing an electrolytic capacitor according to one example includes step (A) of preparing an anode body 1 having a porous portion and a dielectric layer 3 covering at least a portion of the anode body 1, and step (B) of forming a solid electrolyte layer 4 covering at least a portion of the dielectric layer 3. Step (B) includes at least a step of forming a first layer.
[0060] Step (A) (Formation of anode body) An anode body 1 having a porous portion is prepared. For example, a porous sintered body having a predetermined shape obtained by molding and sintering metal particles can be used as the anode body 1. A first portion 2a of an anode wire 2 is embedded in the porous sintered body, and a second portion thereof is led out to the outside.
[0061] (Formation of dielectric layer) Next, the anode body 1 is subjected to a chemical conversion treatment, and at least a portion of the anode body 1 is covered with a dielectric layer 3. Specifically, the anode body 1 is immersed in a chemical conversion tank filled with an aqueous electrolytic solution (e.g., an aqueous phosphoric acid solution), the second portion 2b of the anode wire 2 is connected to an electrode of the chemical conversion tank, and anodization is performed, whereby the dielectric layer 3 made of an oxide film of a valve metal can be formed on the surface of the porous portion.
[0062] Step (B) (Formation of solid electrolyte layer) (Formation of the first layer) The step of forming the first layer 4a may be performed by "in situ polymerization". That is, raw material monomers of the first conductive polymer may be chemically polymerized in a state where the dielectric layer 3 is in contact with a polymerization liquid. The polymerization liquid contains raw material monomers, a first dopant, a polyalkylene glycol, and a silane compound. The polymerization liquid may contain water or an organic solvent such as alcohol as a solvent.
[0063] For example, the anode body 1 is impregnated with a polymerization solution, and a raw material monomer is polymerized on the surface of the dielectric layer 3, thereby forming the first layer 4a so as to cover the dielectric layer 3. In this case, the first dopant may act as an oxidizing agent for the first conductive polymer to be produced, and may be doped into the first conductive polymer as an anion. Specific examples of such a first dopant include naphthalenesulfonic acid, p-toluenesulfonic acid, or salts or complexes thereof. An oxidizing agent other than the first dopant may be used.
[0064] The "in situ polymerization" is not limited to chemical polymerization, and may be performed by electrolytic polymerization. Also, the first layer 4a may be formed by attaching a liquid containing the first conductive polymer and the first dopant, which have been polymerized in advance, to the dielectric layer 3, instead of forming the first layer 4a by "in situ polymerization".
[0065] After the formation of the first layer, drying may be carried out after or simultaneously with the reduced pressure treatment in order to remove the solvent of the polymerization liquid from the first layer.
[0066] (Washing) Next, the anode body 1 on which the first layer 4a has been formed may be washed under predetermined washing conditions. This makes it possible to remove unnecessary components, such as unreacted monomers and unreacted dopants, contained in the first layer 4a. It is preferable to wash the anode body after washing until the measured electrical conductivity falls within a predetermined range when the anode body is immersed in a solvent and the electrical conductivity of the solvent is measured.
[0067] (Formation of the second layer) Step (B) may further include a step of forming a second layer 4b after the step of forming the first layer 4a. The step of forming the second layer 4b may be performed, for example, by applying a liquid containing the second conductive polymer and the second dopant to cover at least a part of the first layer 4a.
[0068] For example, a liquid containing the second conductive polymer and the second dopant may be impregnated into the anode body 1 having the dielectric layer 3 on which the first layer 4a is formed, and then dried as necessary to form the second layer 4b so as to cover at least a portion of the first layer 4a.
[0069] The liquid containing the second conductive polymer and the second dopant may be, for example, a liquid in which the second conductive polymer and the second dopant are dispersed or dissolved in a liquid such as water. The second dopant may be in a state in which it is doped into the second conductive polymer. The second conductive polymer doped with the second dopant may be dispersed in a liquid such as water in the form of particles. In this case, the average particle size D50 of the particles is preferably, for example, 0.01 μm or more and 0.5 μm or less. Here, the average particle size D50 is the median diameter in the volume particle size distribution measured by a particle size measuring device using a dynamic light scattering method.
[0070] After the formation of the second layer, drying may be carried out after or simultaneously with the reduced pressure treatment in order to remove liquid components from the second layer.
[0071] (Addition of basic compounds) Prior to the formation of the second layer, a basic compound may be attached to the first layer. The cations derived from the basic compound suppress the electrostatic repulsion between the anionic first dopant in the first layer and the anionic second dopant in the second layer, thereby enhancing the adhesion between the first layer and the second layer.
[0072] A solution containing a basic compound may be applied to the first layer. Water may be used as a solvent for the solution. Examples of the basic compound include ammonia and amine compounds. Among them, amine compounds are preferred. The amine compound may be any of primary amines, secondary amines, and tertiary amines. The amine compound may be an aliphatic amine or a cyclic amine. The basic compound may be used alone or in combination of two or more. Specifically, for example, amine compounds or amidine compounds such as N,N-dimethyloctylamine and 1,8-diaminooctane are preferably used.
[0073] After the application of the basic compound, drying may be carried out after or simultaneously with reduced pressure treatment in order to remove the solvent from the solution containing the basic compound.
[0074] (Formation of cathode layer) Next, a carbon paste and a metal paste are applied in that order onto the surface of solid electrolyte layer 4 to form cathode layer 5 composed of carbon layer 5a and metal paste layer 5b. However, the configuration of cathode layer 5 is not limited to this.
[0075] (Lead terminal connection) An anode lead terminal 13 and a cathode lead terminal 14 are prepared, and a second portion 2b of an anode wire 2 extending from an anode body 1 is joined to the anode lead terminal 13 by laser welding or resistance welding. In addition, a conductive adhesive 8 is applied to the cathode layer 5, and then the cathode lead terminal 14 is joined to the cathode portion 7 via the conductive adhesive 8.
[0076] (Formation of exterior body) Capacitor element 10 is placed in a mold, and the material of exterior body 11 (e.g., uncured thermosetting resin and filler) is introduced into the mold by transfer molding, compression molding, or the like to seal capacitor element 10. At this time, a portion of anode lead terminal 13 and cathode lead terminal 14 are exposed from the mold.
[0077] Finally, the exposed portions of anode lead terminal 13 and cathode lead terminal 14 are bent along exterior body 11 to form bent portions. As a result, parts of anode lead terminal 13 and cathode lead terminal 14 are disposed on the mounting surface of exterior body 11. By the above method, the electrolytic capacitor 20 is manufactured.
[0078] (Additional Note) The above description of the embodiments discloses the following techniques. (Technology 1) an anode body having a porous portion; a dielectric layer covering at least a portion of the anode body; a solid electrolyte layer covering at least a portion of the dielectric layer; Equipped with The solid electrolyte layer has a first layer, the first layer includes a first conductive component, a polyalkylene glycol, and a silane compound; The first conductive component includes a first conductive polymer and a first dopant. (Technology 2) 2. The electrolytic capacitor according to claim 1, wherein the polyalkylene glycol comprises polyethylene glycol. (Technology 3) 3. The electrolytic capacitor according to claim 1 or 2, wherein the polyalkylene glycol comprises polypropylene glycol. (Technology 4) The electrolytic capacitor according to any one of techniques 1 to 3, wherein the polyalkylene glycol includes a copolymer of ethylene glycol and propylene glycol. (Technology 5) the solid electrolyte layer further comprises a second layer covering at least a portion of the first layer, the second layer includes a second conductive component different from the first conductive component; The electrolytic capacitor according to any one of techniques 1 to 4, wherein the second conductive component includes a second conductive polymer and a second dopant. (Technology 6) At least a portion of the first layer is filled in voids of the porous portion having the dielectric layer, 6. The electrolytic capacitor according to any one of Techniques 1 to 5, wherein at least a part of the second layer is not filled in the voids but is formed outside the main surface of the porous portion. (Technology 7) The electrolytic capacitor according to claim 2, wherein the number average molecular weight of the polyethylene glycol is 200 or more and 5,000 or less. (Technology 8) The electrolytic capacitor according to claim 3, wherein the number average molecular weight of the polypropylene glycol is 200 or more and 5,000 or less. (Technology 9) The electrolytic capacitor according to technique 4, wherein the copolymer of ethylene glycol and propylene glycol has a number average molecular weight of 1,000 to 3,000. (Technology 10) A step of preparing an anode body having a porous portion and a dielectric layer covering at least a portion of the anode body; forming a solid electrolyte layer covering at least a portion of the dielectric layer; Equipped with forming the solid electrolyte layer includes forming a first layer; the step of forming the first layer includes chemically polymerizing a raw material monomer of a first conductive polymer in a state in which the dielectric layer is in contact with a polymerization liquid; The method for producing an electrolytic capacitor, wherein the polymerization liquid contains the raw material monomer, a first dopant, a polyalkylene glycol, and a silane compound. (Technology 11) the step of forming the solid electrolyte layer includes a step of forming a second layer after the step of forming the first layer, The method for manufacturing an electrolytic capacitor according to technique 10, wherein the step of forming the second layer includes applying a liquid containing a second conductive polymer and a second dopant so as to cover at least a portion of the first layer.
[0079] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0080] Example 1 An electrolytic capacitor was fabricated as follows. (Formation of anode body) Tantalum metal particles were used as the valve metal. The tantalum metal particles were molded into a rectangular parallelepiped so that one end of the anode wire made of tantalum metal was embedded in the tantalum metal particles, and the molded body was then sintered in a vacuum. This resulted in an anode part having an anode body made of a porous sintered body of tantalum and an anode wire whose one end was embedded in the anode body and whose remaining part was planted from one surface of the anode body. The size of the anode body after sintering was approximately a rectangular parallelepiped of about 1.0 mm x 2.3 mm x 1.7 mm. The anode wire was planted from the 1.0 mm x 1.7 mm surface.
[0081] (Formation of dielectric layer) The anode body and a part of the anode wire that was planted from the anode body were immersed in a chemical conversion tank filled with an aqueous phosphoric acid solution, and the other end of the anode wire was connected to the anode body in the chemical conversion tank. Then, anodization was performed to form a uniform dielectric layer of tantalum oxide (Ta2O5) on the surface of the anode body (the surface of the porous sintered body including the inner wall surfaces of the holes) and on the surface of part of the anode wire.
[0082] (Formation of solid electrolyte layer) (Formation of the first layer) A polymerization liquid was prepared by mixing 3,4-ethylenedioxythiophene, the raw material monomer of the first conductive polymer, iron(III) p-toluenesulfonate, the first dopant, PEG with a number average molecular weight of 300, which is a polyalkylene glycol (PAG), 3-glycidoxypropyltrimethoxysilane, a silane compound, and 1-butanol. Iron(III) p-toluenesulfonate also functions as an oxidizing agent. Both ends of the PEG are hydroxyl groups.
[0083] The contents of the components other than 1-butanol in the polymerization liquid are as follows. 3,4-Ethylenedioxythiophene 10% by mass Iron(III) p-toluenesulfonate 50% by mass PEG (number average molecular weight 300) 10% by mass 3-Glycidoxypropyltrimethoxysilane 10% by mass
[0084] After immersing the anode in the polymerization solution, the anode was removed from the polymerization solution and heat-treated in air at 75°C. In this way, the raw material monomer was polymerized on the dielectric layer, forming a first layer containing poly(3,4-ethylenedioxythiophene) (PEDOT) as part of the solid electrolyte layer.
[0085] Next, the anode body on which the first layer was formed was washed with a washing liquid for a predetermined period of time.
[0086] (Formation of the second layer) First, a dispersion of poly(3,4-ethylenedioxythiophene), a second conductive polymer doped with p-toluenesulfonic acid, was prepared (PEDOT / PSS dispersion). After immersing the anode body in the PEDOT / PSS dispersion, the anode body was removed from the PEDOT / PSS dispersion and then dried at 80°C for 20 minutes under atmospheric pressure to form a second layer, forming a solid electrolyte layer.
[0087] (Formation of cathode layer to exterior body) A carbon paste and a silver paste were applied in sequence to the surface of the solid electrolyte layer to form a cathode layer consisting of a carbon layer and a silver paste layer, and a capacitor element was obtained. Next, the anode lead terminal was connected by welding to an anode wire that was planted from the anode body. In addition, after applying a conductive adhesive to the cathode layer, the cathode lead terminal was joined to the cathode part. Then, the capacitor element 10 was placed in a mold, and an exterior body was formed by a transfer molding method, completing the electrolytic capacitor A1.
[0088] Example 2
[0089] An electrolytic capacitor A2 was completed in the same manner as in Example 1, except that the contents of the components other than 1-butanol in the polymerization solution were changed as follows:
[0090] 3,4-Ethylenedioxythiophene 10% by mass Iron(III) p-toluenesulfonate 50% by mass PEG-co-PPG (random copolymer, number average molecular weight 1800) 10% by mass 3-Glycidoxypropyltrimethoxysilane 10% by mass
[0091] Comparative Example 1 An electrolytic capacitor B1 was completed in the same manner as in Example 1, except that the contents of the components other than 1-butanol in the polymerization solution were changed as follows, and neither polyalkylene glycol nor silane compound was added.
[0092] 3,4-Ethylenedioxythiophene 10% by mass Iron(III) p-toluenesulfonate 50% by mass PAG 0% by mass Silane compound 0% by mass
[0093] Comparative Example 2 An electrolytic capacitor B2 was completed in the same manner as in Example 1, except that the contents of the components other than 1-butanol in the polymerization liquid were changed as follows, and the polymerization liquid did not contain a silane compound.
[0094] 3,4-Ethylenedioxythiophene 10% by mass Iron(III) p-toluenesulfonate 50% by mass PEG (number average molecular weight 300) 10% by mass Silane compound 0% by mass
[0095] Comparative Example 3 An electrolytic capacitor B3 was completed in the same manner as in Example 2, except that the contents of the components other than 1-butanol in the polymerization liquid were changed as follows, and no silane compound was added to the polymerization liquid.
[0096] 3,4-Ethylenedioxythiophene 10% by mass Iron(III) p-toluenesulfonate 50% by mass PEG-co-PPG (random copolymer, number average molecular weight 1800) 10% by mass Silane compound 0% by mass
[0097] Comparative Example 4 An electrolytic capacitor B4 was completed in the same manner as in Example 1, except that the contents of the components other than 1-butanol in the polymerization liquid were changed as follows, and no polyalkylene glycol was added to the polymerization liquid.
[0098] 3,4-Ethylenedioxythiophene 10% by mass Iron(III) p-toluenesulfonate 50% by mass PAG 0% by mass 3-Glycidoxypropyltrimethoxysilane 10% by mass
[0099] [evaluation] (Breakdown voltage) In an environment of 20°C, a voltage was applied while increasing at a rate of 1.0 V / sec, and the breakdown voltage (BDV) (V) at which an overcurrent of 0.5 A flows was measured. The results are shown in Table 1.
[0100] [Table 1]
[0101] Table 1 shows that when PAG and a silane compound are used in combination, the BVD is significantly improved, whereas when only one of PAG and a silane compound is used, no significant improvement in the BVD is observed and the BDV may actually decrease.
[0102] (Initial ESR) The initial ESR (mΩ) at a frequency of 100 kHz was measured for the electrolytic capacitors A1 and A2 of Examples 1 and 2 using a four-terminal LCR meter in an environment of 20° C. The results are shown in Table 2.
[0103] [Table 2]
[0104] From Table 2, it can be seen that when PAG and a silane compound are used in combination, from the viewpoint of maintaining a low ESR, it is preferable to use PEG-co-PPG as the PAG rather than PEG, and the ESR can be significantly reduced.
[0105] By using the above-mentioned CP processing, a cross section parallel to the thickness direction of the solid electrolyte layer and perpendicular to the longitudinal direction of the capacitor element was exposed, and the cross section was observed by SEM. It was found that the first layer had an inner layer filled in the voids of the porous portion having the dielectric layer and an outer layer protruding from the main surface Sm of the porous portion having the dielectric layer, and that the second layer was generally formed outside the main surface Sm of the porous portion. [Industrial Applicability]
[0106] INDUSTRIAL APPLICABILITY The present disclosure can be used in electrolytic capacitors having a solid electrolyte, and can be preferably used in solid electrolytic capacitors using an anode body having a porous portion (particularly a porous sintered body). [Explanation of symbols]
[0107] 20: Electrolytic capacitor 10: Capacitor element 1: Anode body 2: Anode wire 2a:First part 2b:Second part 3: Dielectric layer 4: Solid electrolyte layer 4a: 1st layer 104a: Inner layer 104b: Outer layer 4b: 2nd layer 5: Cathode layer 5a: Carbon layer 5b: Metal paste layer 6: Anode part 7: Cathode 8: Conductive adhesive 11: Exterior body 13: Anode lead terminal 14: Cathode lead terminal 14a: Joint
Claims
1. an anode body having a porous portion; a dielectric layer covering at least a portion of the anode body; a solid electrolyte layer covering at least a portion of the dielectric layer; Equipped with The solid electrolyte layer has a first layer, the first layer includes a first conductive component, a polyalkylene glycol, and a silane compound; The first conductive component includes a first conductive polymer and a first dopant.
2. 2. The electrolytic capacitor of claim 1, wherein the polyalkylene glycol comprises polyethylene glycol.
3. 2. The electrolytic capacitor of claim 1, wherein the polyalkylene glycol comprises polypropylene glycol.
4. 2. The electrolytic capacitor of claim 1, wherein the polyalkylene glycol comprises a copolymer of ethylene glycol and propylene glycol.
5. the solid electrolyte layer further includes a second layer covering at least a portion of the first layer, the second layer includes a second conductive component different from the first conductive component; 4. The electrolytic capacitor according to claim 1, wherein the second conductive component includes a second conductive polymer and a second dopant.
6. At least a portion of the first layer is filled in voids of the porous portion having the dielectric layer, 6. The electrolytic capacitor according to claim 5, wherein at least a portion of the second layer is not filled in the voids but is formed outside a main surface of the porous portion.
7. 3. The electrolytic capacitor according to claim 2, wherein the number average molecular weight of the polyethylene glycol is 200 or more and 5,000 or less.
8. 4. The electrolytic capacitor according to claim 3, wherein the number average molecular weight of the polypropylene glycol is 200 or more and 5,000 or less.
9. 5. The electrolytic capacitor according to claim 4, wherein the copolymer of ethylene glycol and propylene glycol has a number average molecular weight of 1,000 to 3,000.
10. A step of preparing an anode body having a porous portion and a dielectric layer covering at least a portion of the anode body; forming a solid electrolyte layer covering at least a portion of the dielectric layer; Equipped with forming the solid electrolyte layer includes forming a first layer; the step of forming the first layer includes chemically polymerizing a raw material monomer of a first conductive polymer in a state in which the dielectric layer is in contact with a polymerization liquid; the polymerization liquid contains the raw material monomer, a first dopant, a polyalkylene glycol, and a silane compound.
11. the step of forming the solid electrolyte layer includes a step of forming a second layer after the step of forming the first layer, 11. The method for manufacturing an electrolytic capacitor according to claim 10, wherein the step of forming the second layer includes applying a liquid containing a second conductive polymer and a second dopant so as to cover at least a portion of the first layer.
Citation Information
Patent Citations
Addition of polymer to thiophene monomer in insitu polymerization
JP2015515746A
Solid electrolytic capacitor with improved leakage current
JP2019533304A